2013
DOI: 10.1371/journal.pone.0067925
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of Alternative Promoters Directs Tissue Specific Expression of Epac2 Isoforms

Abstract: Epac 1 and Epac 2 (Epac1/2; exchange factors directly activated by cAMP) are multidomain proteins that mediate cellular responses upon activation by the signaling molecule cAMP. Epac1 is ubiquitously expressed, whereas Epac2 exhibits a restricted expression pattern. The gene encoding Epac2 gives rise to at least three protein isoforms (Epac2A, Epac2B and Epac2C) that exhibit confined tissue and cell specific expression profiles. Here, we describe alternative promoter usage for the different isoforms of Epac2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 46 publications
(90 reference statements)
0
67
0
Order By: Relevance
“…6,7 In contrast, the epigenetical regulation of Rapgef4 alternative promoters leads to a restricted expression pattern of EPAC2 isoforms. 13 EPAC2B, which is similar to EPAC1 in domain structure, is detected in the adrenal gland and the endocrine pancreas, whereas EPAC2C mRNA was reported only in the liver. 12,14 Nonstandard Abbreviations and Acronyms Compelling evidence indicates that EPAC1 and EPAC2 expression levels change throughout development.…”
Section: Epac Proteins Epac Genes and Tissue Distributionmentioning
confidence: 94%
See 1 more Smart Citation
“…6,7 In contrast, the epigenetical regulation of Rapgef4 alternative promoters leads to a restricted expression pattern of EPAC2 isoforms. 13 EPAC2B, which is similar to EPAC1 in domain structure, is detected in the adrenal gland and the endocrine pancreas, whereas EPAC2C mRNA was reported only in the liver. 12,14 Nonstandard Abbreviations and Acronyms Compelling evidence indicates that EPAC1 and EPAC2 expression levels change throughout development.…”
Section: Epac Proteins Epac Genes and Tissue Distributionmentioning
confidence: 94%
“…Rapgef3 transcription leads to the synthesis of one 4-kb long mRNA, whereas alternative promoter usage and differential splicing of Rapgef4 generate 3 different EPAC2 isoforms (named EPAC2A, EPAC2B, and EPAC2C). 12,13 EPAC1 and EPAC2 exhibit distinct expression profiles that may vary depending on developmental stages and pathophysiological situations. EPAC1 is nearly ubiquitously expressed with high levels of expression in the heart, blood vessels, uterus, kidney, and central nervous system.…”
Section: Epac Proteins Epac Genes and Tissue Distributionmentioning
confidence: 99%
“…A few studies in plants and mammals have suggested that promoter methylation changes might influence alternative mRNA isoform transcription Hoivik et al, 2013;Connolly et al, 2011), a possibility we therefore examined for DCL4 transcriptional start sites (TSSs). Analysis of the DCL4 locus revealed a discrete methylation patch affecting cytosines in CG, CHG, and CHH contexts immediately upstream of the coding sequence (Stroud et al, 2013) (Figure 1C; Supplemental Figure 2).…”
Section: Dna Methylation Status Influences Dcl4 Tss Usagementioning
confidence: 99%
“…DNA methylation control of alternative TSS expression is a fascinating concept that is just starting to emerge: Only two such examples are available in metazoans (Hoivik et al, 2013;Connolly et al, 2011), and two imprinted genes were recently shown to undergo this type of regulation in rice (Oryza sativa) endosperm, although the functional significance of alternative TSS isoforms was not elucidated in this instance . While expression studies on RdDM mutants did not detect profound gene expression changes (Reinders et al, 2009;Stroud et al, 2014), such studies would have unlikely revealed subtle changes in TSS usage such as DCL4 Δ and DCL4 NLS .…”
Section: An Unexplored Aspect Of Epigenetic Regulation?mentioning
confidence: 99%
“…SF-1 is highly expressed in steroidogenic cell types where it functions to help control the tissue-specific expression of genes involved in the steroid hormone biosynthesis pathway [90,91]. Additionally, gene knockout studies in mice showed that SF-1 is critical for development and differentiation of the endocrine and reproductive systems, demonstrating it has multiple functions [92].…”
Section: Zinc-finger Transcription Factors Involved In Star Gene Exprmentioning
confidence: 99%